1998
DOI: 10.1177/1081180x98003002006
|View full text |Cite
|
Sign up to set email alerts
|

Public Journalism and Public Knowledge

Abstract: Public journalism is challenging the more traditional notions of mainstream journalism. It represents an attempt to connect journalists with the communities within which they operate. It places citizen input at the center of journalistic concerns. In this essay, we examine the origin and development of public journalism. We note a few of the similarities in this movement to the early muckrakers operating at the turn of the century. We then consider the state of public political knowledge and how this affects p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…For public journalism to be mainstreamed, it will need a higher profile in journalism training so that newer generations of reporters are exposed to it and develop public journalism skills. Eksterowicz et al (1998) state that journalism and communication programs continue to put forward journalistic impartiality and neutrality as the ideal model, and they argue for a new, cross-disciplinary cooperation in public journalism education at the tertiary level. Clearly, new models of training and education that encompass public journalism will address the tension between so-called journalistic objectivity and the journalist as an activist in political dialogue with public audiences.…”
Section: Resultsmentioning
confidence: 98%
“…For public journalism to be mainstreamed, it will need a higher profile in journalism training so that newer generations of reporters are exposed to it and develop public journalism skills. Eksterowicz et al (1998) state that journalism and communication programs continue to put forward journalistic impartiality and neutrality as the ideal model, and they argue for a new, cross-disciplinary cooperation in public journalism education at the tertiary level. Clearly, new models of training and education that encompass public journalism will address the tension between so-called journalistic objectivity and the journalist as an activist in political dialogue with public audiences.…”
Section: Resultsmentioning
confidence: 98%
“…Public journalism scholars frequently invoke the decline in voter participation during political elections in particular, as well as the decline in civic participation in local community affairs more generally, as evidence of widespread public alienation from the democratic process (e.g., Charity, 1995; Merritt, 1998;Rosen, 1996). These scholars also invoke the news media's much-criticized coverage of the 1988 U.S. presidential elections, and results from a study by the Times-Mirror Center (1994), which found that the majority of respondents agreed that "the news media gets [sic] in the way of society solving its problems" (p. 178), as evidence of widespread public dissatisfaction with how mass-mediated political discourse is presently conducted (e.g., Coleman, 1997;Eksterowicz, Roberts, & Clark, 1998;Glasser & Craft, 1998;Lambeth, 1998a;Merritt, 1998;Rosen, 1992Rosen, , 1995Rosen, , 1996Schudson, 1998;Willey, 1998).…”
Section: The Theory and Practice Of Public Journalismmentioning
confidence: 99%
“…Although no one has so far addressed this issue in detail, the literature on public journalism suggests that journalists should engage citizens in their capacity as members of specific communities-a term I use to connote fields of local, multiple interests that may, alternately, both inclusively affiliate and exclusively conflict with each other. The literature on public journalism abounds with references to ideals such as community attachment, community connectedness, and the like, which imply that journalistic coverage of politics should be grounded in particular community values (e.g., Charity, 1995; Eksterowich, Roberts, & Clark, 1998;Fouhy, 1994;Merritt, 1998;Rosen, 1993Rosen, , 1994Rosen, , 1996. Yet, how public journalism scholars conceive of a community remains unclear.…”
Section: Public Journalism Between Universality and Particularitymentioning
confidence: 99%
“…The civic, or public journalism movement, allows the concerns of citizens to help shape the news agenda [3,4,5]. The presidential election in 1988 is often cited as the time civic journalism emerged.…”
Section: Antecedents To Participatory Journalismmentioning
confidence: 99%
“…During this time journalists raised concerns that the election news being covered wasn't news that was of interest to citizens, and that journalists hadn't remembered the public in their coverage [5]. The rise of civic journalism was spurred by declining newspaper readership and increased competition in the delivery of news, particularly 24 hour news stations like CNN [3].…”
Section: Antecedents To Participatory Journalismmentioning
confidence: 99%